PREPARATION AND CHARACTERIZATION OF EGGSHELLS POWDERS TREATED WITH HYDROCHLORIC ACID AND SODIUM HYDROXIDE - Dimitrina Kiryakova; Ganka Kolchakova (Advanced Engineering Letters, 2023)
The present paper investigates the possibility of increasing the porous and surface characteristics of eggshell powders. For this purpose, the collected waste eggshells were washed, dried at 90°C, crushed mechanically and sieved into a particle size smaller than 0.315 µm. The resulting powder was chemically modified by immersion in 1M solutions of HCl and NaOH. After the treatment with the above reagents, the surface-treated eggshells were characterized by a combination of XRD, FT-IR, BET and SEM analyses. The XRD diffraction data and FT-IR spectra confirmed that the untreated eggshells were composed mainly of calcium carbonate in the form of calcite. After treatments on the surface of the particles were carried out, calcite did not undergo structural changes. From the N2 adsorption-desorption isotherms it was found that all of samples have nonporous or macro porous structures.